Incorporating end-users' voices into the development of an implant for HIV prevention: a discrete choice experiment in South Africa and Zimbabwe - Erica N. Browne; Kgahlisho Manenzhe; Wanzirai Makoni; Sikhanyisiwe Nkomo; Imelda Mahaka; Khatija Ahmed; Mary Kate Shapley-Quinn; Tozoe Marton; Ellen Luecke; Leah Johnson; Ariane van der Straten; Alexandra M. Minnis (BMC, 2023)
Abstract Background Input from end-users during preclinical phases can support market fit for new HIV prevention technologies. With several long-acting pre-exposure prophylaxis (PrEP) implants in development, we aimed to understand young women's preferences for PrEP implants to inform optimal design. Methods We developed a discrete choice experiment and surveyed 800 young women in Harare, Zimbabwe and Tshwane, South Africa between September-November 2020. Women aged 18-30 years who were nulliparous, postpartum, or exchanged sex for money, goods or shelter in prior year were eligible; quotas were set for each subgroup. The DCE asked participants to choose between two hypothetical implants for HIV prevention in a series of nine questions. Implants were described by: size, number of rods and insertion sites, duration (6-months, 1-year, 2-years), flexibility, and biodegradability. Random-parameters logit models estimated preference weights. Results Median age was 24 years (interquartile range 21-27). By design, 36% had used contraceptive implants. Duration of protection was most important feature, with strong preference for a 2-year over 6-month implant. In Zimbabwe, the number of rods/insertion sites was second most important and half as important as duration. Nonetheless, to achieve an implant lasting 2-years, 74% were estimated to accept two rods, one in each arm. In South Africa, preference was for longer, flexible implants that required removal, although each of these attributes were one-third as important as duration. On average, biodegradability and size did not influence Zimbabwean women's choices. Contraceptive implant experience and parity did not influence relative importance of attributes. Conclusions While duration of protection was a prominent attribute shaping women's choices for PrEP implants, other characteristics related to discreetness were relevant. Optimizing for longest dosing while also ensuring minimal detection of implant placement seemed most attractive to potential users.